2009
DOI: 10.3310/hta13100
|View full text |Cite
|
Sign up to set email alerts
|

Routine antenatal anti-D prophylaxis for RhD-negative women: a systematic review and economic evaluation

Abstract: How to obtain copies of this and other HTA Programme reports. An electronic version of this publication, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable CD-ROM is also available (see below).Printed copies of HTA monographs cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our Despatch Agents.Non-UK purchasers will have to pay a small fee for post and packing. For Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 214 publications
1
73
0
Order By: Relevance
“…he has one RhD-positive gene and one RhD-negative gene) his children will have a 50% chance of being RhD-negative. Therefore, as in the NICE TA156, 62 the model assumes that the proportion of RhD-positive babies born to RhD-negative women is a function of (1) the proportion of RhD-positive men (assumed to be identical to the proportion of RhD-positive women, thus, the complement of the proportion of RhD-negative women), (2) the proportion of heterozygous fathers and (3) the proportion of heterozygous fathers having RhD-positive babies. Although the probability of having a RhD-positive baby in subsequent pregnancies can be estimated conditional on knowledge of the RhD status of the first baby, we do not split the cohort in this way.…”
Section: Proportion Of Rhd-positive Babies Born To Rhd-negative Womenmentioning
confidence: 99%
See 4 more Smart Citations
“…he has one RhD-positive gene and one RhD-negative gene) his children will have a 50% chance of being RhD-negative. Therefore, as in the NICE TA156, 62 the model assumes that the proportion of RhD-positive babies born to RhD-negative women is a function of (1) the proportion of RhD-positive men (assumed to be identical to the proportion of RhD-positive women, thus, the complement of the proportion of RhD-negative women), (2) the proportion of heterozygous fathers and (3) the proportion of heterozygous fathers having RhD-positive babies. Although the probability of having a RhD-positive baby in subsequent pregnancies can be estimated conditional on knowledge of the RhD status of the first baby, we do not split the cohort in this way.…”
Section: Proportion Of Rhd-positive Babies Born To Rhd-negative Womenmentioning
confidence: 99%
“…62 No new systematic reviews of RAADP with studies not considered in TA156 were identified. We maintain consistency between the NICE TA process and the diagnostics assessment of high-throughput NIPT for fetal rhesus D status by utilising the RAADP …”
Section: Effectiveness Of Anti-d Immunoglobulinmentioning
confidence: 99%
See 3 more Smart Citations